2011
DOI: 10.1258/ebm.2011.011105
|View full text |Cite
|
Sign up to set email alerts
|

Solidago chilensis Meyen hydroalcoholic extract reduces JNK/IκB pathway activation and ameliorates insulin resistance in diet-induced obesity mice

Abstract: Hydroalcoholic extract of Solidago chilensis (Sc) is employed in popular medicine to treat inflammatory disease. The low-grade proinflammatory state and the activation of serine/threonine kinases in adipose tissue, like c-jun kinase (JNK) and IKK, and transcription factors, have an important role in obesity-associated insulin resistance. The aim of this study was to further investigate the effects of the Sc extract on glucose homeostasis in diet-induced obesity mice. Male Swiss mice were randomized to three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…In addition, celastrol also markedly increased the adiponectin gene expression that is associated with increased plasma levels of adiponectin, all of which are related with improved insulin resistance. These results agree with those of a previous study that demonstrated that NF-κB levels were higher in mice treated with a high fat diet, and that inhibition of NF-κB restored the lipotoxicity of adipose tissue and decreased fat mass [39]. Furthermore, celastrol treatment significantly decreased the levels of SFAs, and increased the levels of MUFAs in hepatic and adipose tissue, that are more anti-inflammatory fatty acid composition.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, celastrol also markedly increased the adiponectin gene expression that is associated with increased plasma levels of adiponectin, all of which are related with improved insulin resistance. These results agree with those of a previous study that demonstrated that NF-κB levels were higher in mice treated with a high fat diet, and that inhibition of NF-κB restored the lipotoxicity of adipose tissue and decreased fat mass [39]. Furthermore, celastrol treatment significantly decreased the levels of SFAs, and increased the levels of MUFAs in hepatic and adipose tissue, that are more anti-inflammatory fatty acid composition.…”
Section: Discussionsupporting
confidence: 92%
“…To study the signaling pathway involved in the pathophysiological processes of NAFLD induced by the elevation of FFA and the effects of SAMC intervention, we measured the phosphorylation status and total expression of MAPK kinases signaling pathways including p38 MAPK, JNK and MEK/ERK, which play important roles in insulin and inflammatory responses [18, 19]. Interestingly, our result showed that an increase in the phosphorylation level of p38 MAPK and JNK/c-Jun, but a decrease in the phosphorylation of MEK/ERK1/2 was observed in NAFLD rat liver tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Its main chemical constituents are acetophenone, carotenes, diterpenoids with labdanic and clerodanic skeletons (Soares-Valverde et al, 2009), flavonoids, glycosides, 3-methoxybenzaldehyde, essential oils, and saponins (Silva et al, 2010), with quercetrin being the major constituent (Torres et al, 1987 Ethnopharmacological investigations have found this species to have antispasmodic, antihemorrhagic (Alonso, 1998), woundhealing (Facury-Neto et al, 2004, and anti-inflammatory effects (Tamura et al, 2009). Recently, there has been considerable progress in the investigation of S. chilensis and gastric protection (Bucciarelli et al, 2010) as well as a better understanding of the effect of S. chilensis on insulin resistance in obese mice (Melo et al, 2011). However, the hypoglycemic and hypolipidemic effects of S. chilensis on the glucose tolerance curve have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%